Measuring Productivity In Food Smme Using The Apc Method - Ma’arif Ubaidillah Syakur, Achmad; Catur Wahyuni, Hana (Research Parks Publishing LLC, 2025)
This research was conducted due to the condition of the company which was only founded in June, so that in July the company received few orders and in the following month, namely August, the company received quite a lot of orders and so this research uses a base period in September because the company received 500 orders. pcs and in October the company received a decrease in orders so it experienced a decrease in profits. Therefore this research aims to measure the company's productivity and profitability based on changes in labor, material, energy, capital and total input at UD. Lontong Irfan. The method used involves calculating productivity and profitability indices as well as evaluating price improvement indices to evaluate the impact of changes in input costs. The analysis results show that labor productivity remains stable despite an increase in wages, while material profitability has increased but productivity has decreased. Energy and capital productivity remained stable with no decline in profitability. Although total input productivity decreased, profitability increased, highlighting the complexity of the influence of input variables on a company's overall performance.